Marital Abuse: Its Impact on Wife’s Right to her Dowry in Islamic Family Law - Dwairi, Orwah Nassir (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: The prime purpose of the present study is to critically address how the two Sharia arbitrators determine the percentage of marital abuse with a focus on its legal impacts on wife’s right to her dowry. Methods: Qualitative and quantitative research methods were applied in order to support and strengthen the arguments of the present study. It is highly important to jurisprudentially contextualise the issue of marital discord and conflict within the Islamic Fiqh. The researcher argues that Article No. 126 of Jordan’s Family Law No. 15 of 2019 is not effective enough in addressing cases of marital abuse because there is a steady increase in rates of the divorce based on issues of the marital discord and conflict in Jordan. Results: This study has come to the result that the two Sharia arbitrators’ report does not comply with Sharia guideline and Fiqh conditions in protecting wife’s right to her dowry. It is the contention of the researcher that the prompt and deferred dowry is the wife’s inalienable right in the Holy Quran and Sunnah. Thus, Article No. 126 needs to be reviewed to be more compatible with Islamic Law. Conclusions: Therefore, this study highly concludes that the determination of percentage of marital abuse in Sharia arbitration must be abolished and therefore the role of arbitrators should be restriced to the process of marital reconciliation, if applicable, such that it becomes more compatible with Islamic Fiqh.